VOLATILE ORGANIC COMPOUNDS AND ANTIOXIDANT CAPACITY OF Curcuma longa L. AND Curcuma caesia Roxb. LEAVES: EXPLORING BIOACTIVITY IN NATURAL PRODUCTS - Braga, Monick Cristina; Belo, Lúcio; Soares Júnior, Manoel Soares; Sánchez, Germán Dario Galvis; Pereira, Julião; Oliveira, Tatianne Ferreira de (REVISTA DE AGRICULTURA, 2023)
Natural products contain diverse bioactive compounds with therapeutic and pharmacological potential, including antimicrobial, antioxidant, anticancer, antifungal properties, and respiratory benefits for conditions. Bioactive volatile organic compounds were identified using headspace-gas chromatography in Curcuma longa L (CL). and Curcuma caesia Roxb. (CC) leaves, with CL leaves containing 90.48% terpenes and CC leaves containing 77.5% terpenes and 22.5% non-terpenes. The total phenolic content and antioxidant capacity were evaluated, employing a 2x7 factorial design analyzed through one-way and factorial ANOVA. Methanol:water and ethanol extracts from CL exhibited superior radical sequestering capacity (IC50 of 0.35 mg mL-1) compared to CC extracts. The highest Ferric Reducing Antioxidant Power value of 95.28 µMol FeSO g-1 was achieved analyzing methanol:water. Ethanol:water was considered most appropriate, as it is the most suitable solvents for industrial food processing due to safety and compatibility aspects. Natural products contain diverse bioactive compounds with therapeutic and pharmacological potential, including antimicrobial, antioxidant, anticancer, antifungal properties, and respiratory benefits for conditions. Bioactive volatile organic compounds were identified using headspace-gas chromatography in Curcuma longa L (CL). and Curcuma caesia Roxb. (CC) leaves, with CL leaves containing 90.48% terpenes and CC leaves containing 77.5% terpenes and 22.5% non-terpenes. The total phenolic content and antioxidant capacity were evaluated, employing a 2x7 factorial design analyzed through one-way and factorial ANOVA. Methanol:water and ethanol extracts from CL exhibited superior radical sequestering capacity (IC50 of 0.35 mg mL-1) compared to CC extracts. The highest Ferric Reducing Antioxidant Power value of 95.28 µMol FeSO g-1 was achieved analyzing methanol:water. Ethanol:water was considered most appropriate, as it is the most suitable solvents for industrial food processing due to safety and compatibility aspects.